(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Laboratory experiments of wave energy converters (WECs) are subject to many sources of uncertainty from the wave to the wire. These uncertainties are inherent due to the accuracy of the sensors that collect measurements and the repeatability of the experiments. Understanding the uncertainty of common WEC metrics is important for advancing the technological readiness level (TRL) of devices and improving confidence in their performance. Still, relatively little work has been performed in this area and uncertainty often goes unreported. This work aims to demonstrate detailed uncertainty analysis (DUA) on a point absorber WEC which the authors have not seen done, report uncertainties of performance metrics and their major sources, and finally, provide recommendations to reduce uncertainty and inform technical specifications. The experimental testing was conducted with the Laboratory Upgrade Point Absorber (LUPA) WEC at the O.H. Hinsdale Wave Research Laboratory at 3.695 m water depth in the Large Wave Flume in Corvallis, Oregon. LUPA is an open-source, two-body point absorber wave energy converter built by Oregon State University. It has a 1-meter diameter float connected through a belt-driven PTO to a spar with a heave plate. LUPA was moored and operated with six degrees of freedom to represent a more realistic deployment of a floating WEC. Wave conditions varied in nonlinearity and duration to assess their impact on uncertainty in irregular waves. The PTO controls utilized impedance-matched informed values for the velocity-dependent damping and positive and negative position-dependent stiffness to maximize power capture and increase the uncertainty analysis’s complexity and applicability. The main performance metrics to be analyzed are capture width and its derivatives: WEC power capture and incident wave power. The epistemic and aleatoric uncertainty(ies) for each variable in the metrics will be found via engineering data and repeat wave conditions, respectively, following the International Tank Towing Conference and the International Electrotechnical Commission guidelines for uncertainty analysis of wave energy converters. The uncertainties will be combined and propagated using the Monte Carlo Method, a method adopted by other industries for uncertainty propagation that should be considered for marine energy standards. Uncertainty analysis following this process has already been completed for LUPA in regular waves and this paper seeks to expand this work for irregular waves.